2020
DOI: 10.1186/s12883-020-01972-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on intracranial pressure and prognosis in patients with severe brain diseases undergoing endotracheal suctioning

Abstract: Background To investigate whether the administration of intravenous propofol before endotracheal suctioning (ES) in patients with severe brain disease can reduce the sputum suction response, improve prognosis, and accelerate recovery. Methods A total of 208 severe brain disease patients after craniocerebral surgery were enrolled in the study. The subjects were randomly assigned to the experimental group (n = 104) and the control group (n = 104). The experimental group was given intravenous propofol (10 ml pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Propofol can inhibit the extracellular voltage dependent calcium channel from entering calcium ions, playing the role of calcium ion flow and reducing calcium overload. In this way, brain tissue and brain cell functions can be effectively protected, and a large amount of sodium and water can be effectively prevented from remaining in cells, thus effectively reducing brain edema and improving brain oxygen metabolism and intracranial pressure [ 7 ].…”
Section: Related Workmentioning
confidence: 99%
“…Propofol can inhibit the extracellular voltage dependent calcium channel from entering calcium ions, playing the role of calcium ion flow and reducing calcium overload. In this way, brain tissue and brain cell functions can be effectively protected, and a large amount of sodium and water can be effectively prevented from remaining in cells, thus effectively reducing brain edema and improving brain oxygen metabolism and intracranial pressure [ 7 ].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, keeping these patients adequately sedated can reduce brain metabolism, avoid ventilator asynchrony and venous congestion, preventing elevation of thoracic pressure, contributing to the intracranial compartment compliance. In many studies, propofol has shown to reduce ICP and cerebral metabolic rate of oxygen (CMRO2) (Wu et al, 2020). Side effects of propofol are dose-dependent hypotension which can decrease cerebral perfusion pressure even if it induces a decrease in ICP and dose-dependent respiratory depression (Peluso et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition to the fast-acting sedative effects of the drug 30-60 seconds typically, propofol is also metabolized by the body quickly. 6 The sedative properties of the drug increase patient comfort and assist with better ventilator compliance. Additionally, propofol can also lower ICP by decreasing cerebral blood flow.…”
Section: Titrating Medicationsmentioning
confidence: 99%
“…Propofol is a short-acting sedative/anesthetic drug that's commonly used in the ICU setting with ventilated patients 5. In addition to the fast-acting sedative effects of the drug 30–60 seconds typically, propofol is also metabolized by the body quickly 6. The sedative properties of the drug increase patient comfort and assist with better ventilator compliance.…”
Section: Titrating Medicationsmentioning
confidence: 99%